A Generalized Interest Rates Model with Scaling - Wang, Guizhou; Hausken, Kjell (International Journal of Economics and Financial Issues, 2022)
The article introduces scaling and generalizes the Taylor (1993) interest rate rule from four terms to seven terms. The three additional terms are the deviation in money supply, the deviation in money velocity, and the deviation in unemployment rate. The four original terms are the inflation rate, the equilibrium real interest rate, the deviation in inflation rate, and the deviation in real GDP (Gross Domestic Product). The weights for the seven terms are estimated via the monthly January 1, 1959 - March 31, 2022 US data. All the seven combinations of the Taylor (1993) rule, the Quantity Equation (Friedman, 1970), and the Phillips (1958) curve with scaling give substantially better results than both Taylor (1993, 1999) rules without scaling. The Phillips (1958) curve is best when choosing only one rule with scaling. Combining the Taylor (1993) rule and the Phillips (1958) curve is best when choosing among two rules with scaling.